2014
DOI: 10.1088/0957-0233/25/5/055107
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the magnetic polarizability tensor and three dimensional object location for multiple objects using a walk-through metal detector

Abstract: A previously reported tomographic metal detector which is capable of inverting the location and magnetic polarizability tensor for a single object has been modified such that it is capable of inverting the location and magnetic polarizability tensor for multiple objects. In this paper, the term ‘multiple objects’ refers to up to three independent metallic objects. The results from this paper show that the algorithm works well for objects vertically separated by greater than 40 cm, however the reliability varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…The inversion problem was to determine the tensor components and the 3D coordinate sequence of the metal object as it was carried through the portal. A subsequent report (Marsh, Ktistis, J€ arvi, Armitage, & Peyton, 2014) showed that multiple metal objects could be characterised and positioned simultaneously in this manner.…”
Section: Metal Detectionmentioning
confidence: 97%
“…The inversion problem was to determine the tensor components and the 3D coordinate sequence of the metal object as it was carried through the portal. A subsequent report (Marsh, Ktistis, J€ arvi, Armitage, & Peyton, 2014) showed that multiple metal objects could be characterised and positioned simultaneously in this manner.…”
Section: Metal Detectionmentioning
confidence: 97%
“…The simultaneous identification of multiple unexploded ordnance has been considered in [18], where an MPT representation, in which the coupling between the eddy currents in multiple bodies is neglected, has been applied. The group of Peyton has applied real-time MPT inversion and classification of multiple objects to the problem of security screening [26]- [29], [45] and is developing techniques for measuring MPTs for a range of threat and nonthreat items illuminated by harmonic fields, in the lab [1], [16] and field. The group of Bilas and Vasić has also made field measurements of MPTs for a range of objects using harmonic and impulse excitation [2] and is developing systems for mine clearance in partnership with the group of Peyton.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been used to improve electrical imaging [1] (for biomedical or industrial purposes) as well as investigating electrosensing fish [2,3,4,5,6,7] and also metal detection for security screening [8,9,10] or landmine clearance [11,12,13]. It arises from the studies about the perturbation of electric or electromagnetic field in a free space (such as 2D or 3D) due to the conductivity contrast between the space itself and some small conducting objects.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples regarding computation of the PT based on the explicit formula and according to the geometry as well as the material of a conducting object can be found in [17,20,21,22,23]. On the other hand, the PT is sometimes referred as the polarizibility tensor in engineering literatures and can be obtained from field measurements either in laboratory or fieldwork [8,9,10,12,13]. Since the measurements can be made as long as there is a conducting object perturbing the electric or electromagnetic field, any other information about the object is not needed to find the PT (see Makkonen et al [10]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation